Risk-adapted management of data flow parameters of infocommunication networks in critical infrastructure systems - Kosenko, V.; Nevliudov, I. (ISMA, 2020)
The monograph deals with the problems of adaptive control of data flow parameters to ensure the requirements for promptness and exchange of high-risk information in critical communications infrastructure networks. The method of adaptive management of the distribution of information flows allows to consider for different types of communication channels the possible change of requirements of application tasks or user activity and solves the optimization problem of reducing the total data transmission costs. A method based on causal analysis theory is used to determine the category of critical infrastructure in the risk scale. The description of information technology of risk-adaptive data flow management of the infocommunication network is given.
Keywords: infocommunication network; risk analysis; information systems; traffic management; critical infrastructure